Mathematics Communication Ability of Junior High School Students based on Gender in Terms of Solo Taxonomy - Nurul Mumtaha; Usman Aripin (IKIP Siliwangi, 2021)
This study aims to determine mathematics communication ability of junior high school students based on gender in terms of solo taxonomy. In order to do so, we used qualitative method with interviews and tests. The instrument in the study was a communication skill test with 4 items of description based on a solo taxonomy and interview. We conducted the instrument to 30 junior high school students with 15 male students and 15 female students.. The results of this study indicate the percentage of student response quality in completing the written test about the set including male students at the prestructural level as many as 4 students or 26.7%, unistructural level as many as 1 student or 6.6%, multistructural level as many as 4 students or 26, 7%, at the relational level as many as 5 students or 33.3% and at the extended abstract level there is no while for female students at the practructural level as many as 1 student or 6.7%, the unistructural level as much as 1 student 6.7%, multistructural level 4 students or 26.6%, the relational level is 7 students or 64.6% and the extended abstract level is 2 students or 13.4%. Based on the result, we conclude that the quality of the responses of male and female students in solving mathematics are in the relational level, which female students have a higher percentage than male students. They already able to relate the information to solve the problems given by accurate and draw conclusions.